Porous conductive ceramic membrane loaded with photoelectric catalyst and preparation method and application thereof
By loading the photoelectric catalyst on the porous conductive ceramic membrane, the problems of low conductivity and low hydrogen evolution efficiency shown by the photoelectric catalyst in the prior art are solved, and efficient and stable hydrogen production performance is achieved.
Patent Information
- Application Number
- CN202010893432.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-08-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2040-08-31
AI Technical Summary
The existing photoelectric catalysts exhibit low conductivity, low hydrogen evolution efficiency and inability to resist strong acids and alkalis on the support, resulting in low efficiency and short service life in the hydrogen production process.
A porous conductive ceramic film loaded with a photoelectric catalyst is prepared by mixing conductive ceramic powder, sintering agent, dispersant, binder and solvent, and then prepared by casting molding and sintering to form high porosity and high porosity. The porous conductive ceramic membrane with specific surface area is then supported by hydrothermal method, electrochemical deposition method or spin coating method and other photoelectro-electro-catalysts.
High strength, high stability, high porosity, high specific surface area, strong acid and alkali resistance, high conductivity and high hydrogen analysis efficiency are achieved, which significantly improves the performance of photoelectric catalysts in the hydrogen production process.
Smart Images

Figure CN114100637B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of conductive ceramic membranes, and in particular to a porous conductive ceramic membrane loaded with a photoelectric catalyst, and a preparation method and application thereof. Background Art
[0002] With the continuous increase in energy demand and the problems of air pollution and global warming caused by traditional fossil energy, the development of new energy has become an important task. Among them, hydrogen energy has attracted much attention due to its advantages of high calorific value and low pollution. Producing hydrogen through efficient solar photolysis and electrolysis of water is one of the important means to solve the energy crisis. Among them, catalysts play a key role in the process of photolysis and electrolysis of hydrogen production. For example, molybdenum sulfide, molybdenum sulfur polyions, titanium dioxide, zinc oxide, tin oxide, zirconium dioxide, cadmium sulfide, precious metals, etc. are all common photoelectric catalysts. Generally, catalysts are used in the form of powders, with low conductivity and hydrogen evolution efficiency, and are not easy to recycle: if loaded on nickel foam, carbon materials and their derivatives, although the conductivity is improved, the carrier strength is low, it is not resistant to strong acids and alkalis, and has low adaptability. Therefore, it is urgent to find a suitable carrier so that the catalyst can play a better role. Summary of the invention
[0003] In order to enable the photoelectrocatalyst to play a better role on a suitable carrier, the purpose of the present invention is to provide a porous conductive ceramic membrane loaded with a photoelectrocatalyst, which has the advantages of high strength, high stability, high porosity, high specific surface area, resistance to strong acids and alkalis, high conductivity, and high hydrogen evolution efficiency.
[0004] Another object of the present invention is to provide a porous conductive ceramic membrane loaded with a photoelectric catalyst.
[0005] Another object of the present invention is to provide an application of the porous conductive ceramic membrane loaded with photoelectrocatalyst.
[0006] To achieve the above-mentioned purpose, on the one hand, the present invention provides a method for preparing a porous conductive ceramic membrane loaded with a photoelectric catalyst, the preparation method comprising the following steps: (1) ball-milling and mixing a conductive ceramic powder, a sintering aid, a dispersant, a binder, and a solvent to obtain a ceramic slurry; (2) the ceramic slurry is subjected to tape casting, curing, and drying to obtain a ceramic membrane blank; (3) the ceramic membrane blank is sintered to prepare a porous conductive ceramic membrane, preferably, the porous conductive ceramic membrane has a porosity of 60-70%; (4) loading a photoelectric catalyst on the porous conductive ceramic membrane to obtain a porous conductive ceramic membrane loaded with a photoelectric catalyst.
[0007] According to some specific embodiments of the present invention, in step (1), the ceramic slurry comprises the following components in parts by weight: 9-11 parts of conductive ceramic powder, 0.4-1.2 parts of sintering aid, 0.3-0.6 parts of dispersant, 1.2-1.9 parts of binder, and 5-9 parts of solvent.
[0008] According to some specific embodiments of the present invention, in step (1), the conductive ceramic powder is selected from one or a combination of two or more of titanium nitride, titanium carbide, tungsten carbide, molybdenum carbide, molybdenum silicide, Ti4AlN3, and Ti3SiC2.
[0009] According to some specific embodiments of the present invention, in step (1), the particle size of the conductive ceramic powder is 2-10 μm, and the purity is 99.95%.
[0010] According to some specific embodiments of the present invention, in step (1), the sintering aid is selected from one or a combination of two or more of oxides, nitrides, and carbides, and is preferably one or a combination of two or more of yttrium oxide, titanium dioxide, silicon carbide, and aluminum oxide.
[0011] According to some specific embodiments of the present invention, in step (1), the dispersant is selected from one or a combination of two or more of polyvinyl pyrrolidone, KD-1 dispersant (Hypermer KD1 dispersant from Croda, UK) and O-(2-aminopropyl)-O`-(2-methoxyethyl) polyethylene glycol.
[0012] According to some specific embodiments of the present invention, in step (1), the binder is selected from one or a combination of two or more of polyethersulfone, polyvinyl butyral and polyvinyl alcohol.
[0013] According to some specific embodiments of the present invention, in step (1), the solvent includes N-methylpyrrolidone.
[0014] According to some specific embodiments of the present invention, in step (1), the ball milling speed is 100-300 r / min, and the ball milling time is 10-48 h.
[0015] According to some specific embodiments of the present invention, the casting operation in step (2) includes the following steps: vacuum degassing the ceramic slurry, then quickly transferring it to a single-layer casting mold, adjusting the scraper height, placing it in water after casting, and completely curing and drying it to form a ceramic membrane blank.
[0016] According to some specific embodiments of the present invention, the scraper height is adjusted to 0.1-10 mm.
[0017] According to some specific embodiments of the present invention, in step (3), the sintering is carried out in a carbon tube furnace with an atmosphere, and the sintering temperature is 1500-1700°C.
[0018] According to some specific embodiments of the present invention, the atmosphere in the carbon tube furnace is nitrogen, the heating rate of the carbon tube furnace is 10-15° C. / min, and the holding time after heating to the sintering temperature is 4-10 h.
[0019] According to some specific embodiments of the present invention, in step (4), the method of loading the photoelectrocatalyst is selected from a hydrothermal method, an electrochemical deposition method, and a spin coating method.
[0020] According to some specific embodiments of the present invention, the supported photoelectrocatalyst includes molybdenum disulfide.
[0021] According to some specific embodiments of the present invention, when molybdenum disulfide is selected as the photoelectric catalyst loaded on the porous conductive ceramic membrane, the hydrothermal method includes the following operating steps: adding ammonium molybdate tetrahydrate, thiourea and deionized water to mix with the porous conductive ceramic membrane, adjusting the pH, transferring to a reactor for hydrothermal reaction, washing and drying the product with deionized water and ethanol, and obtaining a porous conductive ceramic membrane loaded with molybdenum disulfide.
[0022] According to some specific embodiments of the present invention, the mass ratio of ammonium molybdate tetrahydrate to thiourea is 1:(0.8-2.6).
[0023] According to some specific embodiments of the present invention, the pH value is 1-5.
[0024] According to some specific embodiments of the present invention, the hydrothermal reaction temperature is 140-200° C., and the hydrothermal reaction time is 12-24 h.
[0025] According to some specific embodiments of the present invention, when molybdenum disulfide is selected as the photoelectric catalyst loaded on the porous conductive ceramic membrane, the electrochemical deposition method includes the following operating steps: adding ammonium molybdate tetrahydrate, potassium sulfide and deionized water to form an electrolyte, using a three-electrode system, and performing electrodeposition with the porous conductive ceramic membrane as the working electrode, and the product is washed and dried with deionized water and ethanol to obtain a porous conductive ceramic membrane loaded with molybdenum disulfide.
[0026] According to some specific embodiments of the present invention, the mass concentration of ammonium molybdate tetrahydrate prepared by the electrochemical deposition method is 1%-10%, and the mass concentration of potassium sulfide is 5%-20%. The three-electrode system includes a working electrode, a reference electrode and a counter electrode, wherein the reference electrode includes a saturated calomel electrode, the counter electrode includes a graphite rod, the electrodeposition mode is a chronopotentiometry, the electrodeposition potential is -0.2-0.5V, and the electrodeposition time is 500-2400s.
[0027] According to some specific embodiments of the present invention, when molybdenum disulfide is selected as the photoelectric catalyst loaded on the porous conductive ceramic membrane, the spin coating method includes the following operating steps: adding ammonium tetrathiomolybdate and ethylene glycol to form a uniform solution, setting a specific spin coater speed, spin coating on the porous conductive ceramic membrane, and after drying, placing it in a tubular furnace for reduction under a nitrogen and hydrogen atmosphere to obtain a porous conductive ceramic membrane loaded with molybdenum disulfide.
[0028] According to some specific embodiments of the present invention, the mass concentration of ammonium tetrathiomolybdate is 1%-20%, the spin coater speed is set to 1000-3000r / min, the drying temperature is 60-100°C, the drying time is 30min-200min, the atmosphere in the tubular furnace includes 5% hydrogen and 95% nitrogen by volume percentage, the reduction temperature is 300-500°C, and the reduction time is 1-5h.
[0029] On the other hand, the present invention also provides a porous conductive ceramic membrane loaded with a photoelectrocatalyst prepared by the method for preparing the porous conductive ceramic membrane loaded with a photoelectrocatalyst.
[0030] In another aspect, the present invention also provides the use of the above-mentioned porous conductive ceramic membrane loaded with photoelectrocatalyst in hydrogen production by hydrolysis.
[0031] Beneficial effects of the present invention:
[0032] The present invention provides a porous conductive ceramic membrane loaded with a photoelectric catalyst, and a preparation method and application thereof. The preparation method uses conductive ceramic powder as the main raw material, and adds a sintering aid, a dispersant, a binder, and a solvent to prepare a ceramic slurry, and the slurry is tape-cast to obtain a porous titanium nitride green body; then a porous conductive ceramic membrane with high porosity is prepared by high-temperature sintering. The photoelectric catalyst loading is achieved by using a hydrothermal method, impregnation, electrochemical deposition, spin coating and other methods. The present invention has the characteristics of high strength, high stability, high porosity, high specific surface area, strong acid and alkali resistance, high conductivity, and high hydrogen evolution efficiency. It has a good application prospect in the field of electrocatalytic hydrogen evolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a SEM image of porous titanium nitride without molybdenum disulfide loading in Example 1 of the present invention;
[0034] Figure 2 This is a SEM image of a porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide in Example 1 of the present invention;
[0035] Figure 3 This is the XRD diagram of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide in Example 1 of the present invention;
[0036] Figure 4 This is the impedance diagram of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide in Example 1 of the present invention;
[0037] Figure 5 The voltammograms at different scan rates of porous titanium nitride without molybdenum disulfide loading in Example 1 of the present invention;
[0038] Figure 6 The voltammograms at different scan rates of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide in Example 1 of the present invention;
[0039] Figure 7 This is a graph of the double-layer capacitance of porous titanium nitride without molybdenum disulfide loading according to Example 1 of the present invention;
[0040] Figure 8 This is a double-layer capacitance diagram of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide in Example 1 of the present invention;
[0041] Fig. 9 This is the polarization curve of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide in Example 1 of the present invention;
[0042] Fig.10 This is a SEM image of porous titanium carbide without molybdenum disulfide loading in Example 2 of the present invention;
[0043] Fig.11 This is a SEM image of porous titanium carbide loaded with molybdenum disulfide by hydrothermal method in Example 2 of the present invention;
[0044] Fig.12 This is a SEM image of porous titanium carbide loaded with molybdenum disulfide by electrodeposition in Example 2 of the present invention;
[0045] Fig.13 This is a SEM image of porous titanium carbide loaded with molybdenum disulfide by spin coating method in Example 2 of the present invention;
[0046] Figure 14-1 EDS analysis of porous titanium carbide loaded with molybdenum disulfide prepared by electrochemical deposition method in Example 2 of the present invention;
[0047] Figure 14-2 EDS analysis of porous titanium carbide loaded with molybdenum disulfide prepared by electrochemical deposition method in Example 2 of the present invention;
[0048] Figure 14-3 EDS analysis of porous titanium carbide loaded with molybdenum disulfide prepared by electrochemical deposition method in Example 2 of the present invention;
[0049] Figure 15-1 This is the EDS analysis of the porous titanium carbide loaded with molybdenum disulfide prepared by the spin coating method in Example 2 of the present invention;
[0050] Figure 15-2This is the EDS analysis of the porous titanium carbide loaded with molybdenum disulfide prepared by the spin coating method in Example 2 of the present invention;
[0051] Figure 15-3 This is the EDS analysis of the porous titanium carbide loaded with molybdenum disulfide prepared by the spin coating method in Example 2 of the present invention;
[0052] Fig.16 This is a comparison diagram of polarization curves of electrocatalytic hydrogen evolution of porous titanium carbide loaded with molybdenum disulfide by three methods and porous titanium carbide without loading in Example 2 of the present invention;
[0053] Fig.17 This is a comparison chart of Tafel data of electrocatalytic hydrogen evolution of porous titanium carbide loaded with molybdenum disulfide by three methods in Example 2 of the present invention and porous titanium carbide without loading. DETAILED DESCRIPTION
[0054] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the present invention / technical solution is described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0055] Example 1
[0056] This embodiment provides a preparation method of a porous titanium nitride ceramic loaded with molybdenum disulfide and a hydrogen production test, which are as follows:
[0057] Titanium nitride powder with an average particle size of 2.5 μm, yttrium oxide powder and titanium dioxide powder accounting for 5% of the mass of the titanium nitride powder (molar ratio of 1:1), polyvinyl pyrrolidone accounting for 4% of the mass of the titanium nitride powder as a dispersant, polyether sulfone accounting for 16% of the mass of the titanium nitride powder as a binder, and N-methylpyrrolidone accounting for 65% of the mass of the titanium nitride powder as a solvent are selected and poured into a ball mill for ball milling. The ball mill speed is 300 r / min and the operation is carried out for 48 hours; the ball-milled slurry is placed on a tape-casting molding equipment designed and assembled in the laboratory for tape-casting molding, the scraper height is adjusted to 1 mm, and then placed in water for curing for 10 hours. The cured green body is placed at room temperature for drying for 48 hours; the dried green body is heated to 1700°C at a heating rate of 10°C / min in a nitrogen furnace and kept warm for 4 hours to obtain a porous titanium nitride ceramic. Weigh ammonium molybdate tetrahydrate and thiourea (mass ratio of 1:1.7), add deionized water, add hydrochloric acid to adjust the pH to 5, put it into a polytetrafluoroethylene stainless steel autoclave together with the porous titanium nitride ceramic, and then put it into an oven, the reaction temperature is 200°C, and the reaction time is 24h. The porous titanium nitride ceramic loaded with molybdenum disulfide is obtained, washed with deionized water, and dried at 80°C.
[0058] The structure and properties of the porous titanium nitride supported by molybdenum disulfide prepared in this example are characterized as follows:
[0059] Figure 1This is the SEM image of the porous titanium nitride without molybdenum disulfide loading in this embodiment. Figure 2 This is the SEM image of the porous titanium nitride electrocatalytic hydrogen evolution electrode loaded with molybdenum disulfide in Example 1. It is found that molybdenum disulfide grows on the surface and in the pores of the porous titanium nitride to form a flower-like structure, so it has a large specific surface area, which is beneficial to improving the hydrogen evolution efficiency.
[0060] Figure 3 This is the XRD pattern of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide in this embodiment. The figure has five diffraction peaks at 2θ=36.30°, 42.22°, 61.26°, 73.44°, and 77.23°, corresponding to the (111), (200), (220), (311), and (222) crystal planes of TiN, respectively; the figure has three diffraction peaks at 2θ=13.87°, 33.05°, and 59.02°, corresponding to the (002), (101), and (110) crystal planes of MoS2, respectively.
[0061] Figure 4 The impedance diagram of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide in this embodiment is shown. The Nyquist curve is fitted, and the transfer resistance of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide prepared in this embodiment is 12Ω. The lower transfer resistance is conducive to the hydrogen evolution reaction of molybdenum disulfide.
[0062] Figure 5 The voltammograms of porous titanium nitride without molybdenum disulfide supported at different scan rates in this example are shown. Figure 6 The voltammograms at different scan rates of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide in this example. Figure 7 The double-layer capacitance of porous titanium nitride without MoS2 loading in this example is shown in Figure 1. The calculated double-layer capacitance is 45.2 mF·cm -2 . Figure 8 The double-layer capacitance of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide in this embodiment is shown in Figure 2. The calculated double-layer capacitance is 99.1 mF·cm -2 This indicates that the electrode prepared in this embodiment provides a larger reaction area and more active sites in the electrochemical process, thereby accelerating the reaction rate.
[0063] Fig. 9 The polarization curve of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide in this example is shown in Figure 2. -1 The electrocatalytic hydrogen evolution test in H2SO4 solution showed that the current density was 10 mA cm -2The electrode prepared by the present invention has a hydrogen evolution overpotential of 195 mV (vs RHE), which is lower than the molybdenum disulfide catalyst overpotential reported in the literature (337 mV (vs RHE)), and is also significantly improved than the porous titanium nitride ceramic without molybdenum disulfide loading (258 mV (vs RHE)). It can be explained that the electrode prepared in this embodiment enhances the conductivity of molybdenum disulfide, and at the same time, because of the large specific surface area, it provides more catalytic active sites. Molybdenum disulfide and titanium nitride have a synergistic effect, which greatly reduces the hydrogen evolution overpotential.
[0064] Example 2
[0065] This embodiment provides a preparation method of porous titanium carbide ceramic loaded with molybdenum disulfide and a hydrogen production test, which are as follows:
[0066] 46.5 g of titanium carbide powder with an average particle size of 8 μm, 1 g of silicon carbide powder and 2.5 g of yttrium oxide powder, 6.25 g of polyethersulfone as a polymer binder, 2 g of O-(2-aminopropyl)-O'-(2-methoxyethyl)polypropylene glycol as a dispersant, and 41.75 g of N-methylpyrrolidone as a solvent were selected, and a slurry with a solid content of 50% was poured into a ball mill, and alumina ball mill beads were added. The ball mill speed was set to 200 r / min and run for 36 hours; the ball-milled slurry was placed on a tape-casting equipment designed and assembled in the laboratory for tape-casting, the scraper height was adjusted to 0.8 mm, and then placed in water for curing for 4 hours. After solidification, several circular bodies with a radius of 1 cm were cut from the green body and placed in an oven at 80°C for 4 hours. The dried bodies were placed in a vacuum carbon tube furnace and heated to 1700°C at a heating rate of 12°C / min in a nitrogen atmosphere. The temperature was kept at this temperature for 4 hours, and after cooling to room temperature, a sintered circular porous titanium carbide ceramic membrane was obtained.
[0067] Weigh 0.86g of thiourea and 0.5g of ammonium molybdate tetrahydrate, add 40ml of deionized water, adjust pH≈3 with 0.1mol / L hydrochloric acid, stir for 30min, pour into polytetrafluoroethylene stainless steel autoclave, put in the sintered circular porous titanium carbide ceramic membrane, put in an oven, the reaction temperature is 200℃, the reaction time is 12h. After the reaction, take out, wash with alcohol and water three times each, and obtain porous titanium carbide ceramic loaded with molybdenum disulfide prepared by hydrothermal method.
[0068] Weigh 1.928g of ammonium molybdate tetrahydrate and 1.76g of potassium sulfide, add hydrochloric acid to pH≈8, add a certain amount of deionized water to prepare an electrolyte, use a saturated calomel electrode as a reference electrode, a graphite rod as a counter electrode, and a sintered circular porous titanium carbide ceramic membrane as a working electrode. Put it into the electrolyte, set the chronopotentiometry electrodeposition for 600s, and obtain a porous titanium carbide ceramic loaded with molybdenum disulfide prepared by electrochemical deposition.
[0069] Weigh 0.125g of ammonium tetrathiomolybdate and 9.725g of ethylene glycol to prepare an ethylene glycol solution containing 1.25% by mass concentration of ammonium tetrathiomolybdate, take the sintered circular porous titanium carbide ceramic membrane, set the rotation speed to 1500rpm, spin coat it on the surface of the ceramic sheet, bake in an oven at 80°C for 60min, and reduce it in a nitrogen and hydrogen (5% H2+95% N2) atmosphere at 300°C for 1h to obtain a porous titanium carbide ceramic loaded with molybdenum disulfide prepared by spin coating.
[0070] The structures and properties of the porous titanium carbide supported by molybdenum disulfide prepared by the three methods of this embodiment are characterized as follows:
[0071] Fig.10 This is the SEM image of porous titanium carbide without molybdenum disulfide loading in this embodiment. Fig.11 This is the SEM image of porous titanium carbide loaded with molybdenum disulfide by the hydrothermal method in this embodiment. Fig.12 This is the SEM image of porous titanium carbide loaded with molybdenum disulfide by electrochemical deposition method in this embodiment. Fig.13 This is the SEM image of the porous titanium carbide loaded with molybdenum disulfide by the spin coating method of this embodiment; it is found that the three methods all allow molybdenum disulfide to grow on the surface and in the pores of the porous titanium carbide, and obtain different morphologies with a larger specific surface area, which is beneficial to improving the hydrogen evolution efficiency.
[0072] Figure 14-1 , Figure 14-2 and Figure 14-3 EDS analysis of porous titanium carbide loaded with molybdenum disulfide prepared by electrochemical deposition method in this embodiment. According to the results of elemental analysis Figure 14-1 It can be seen that the distribution of sulfur elements is perfectly consistent with the original shape. Figure 14-2 and Figure 14-3 The data on molybdenum-sulfur atom coverage show that a layer of molybdenum disulfide catalyst is evenly loaded on the ceramic surface.
[0073] Figure 15-1 , Figure 15-2 and Figure 15-3 EDS analysis of porous titanium carbide loaded with molybdenum disulfide prepared by spin coating in this embodiment. According to the results of elemental analysis Figure 15-1 It can be seen that the distribution of sulfur elements is perfectly consistent with the original shape. Figure 15-2 and 15-3 The data on molybdenum-sulfur atom coverage show that a layer of molybdenum disulfide catalyst is evenly loaded on the ceramic surface.
[0074] Fig.16The polarization curves of porous titanium carbide loaded with molybdenum disulfide prepared by three methods (hydrothermal method, electrochemical deposition method, spin coating method) and unloaded porous titanium carbide for electrocatalytic hydrogen evolution are compared. The ceramic membrane loaded with catalysts prepared by the three methods was tested for electrolysis of water for hydrogen evolution. As can be seen from the figure, the current density is 10mAcm -2 The overpotential of hydrogen production of the original ceramic membrane was 512mV. After loading the catalyst, the overpotential dropped significantly. The overpotential of the spin coating method was 253mV, the electrodeposition method was 166mV, and the hydrothermal method was 114mV. The performance of water decomposition of hydrogen has been greatly improved.
[0075] Fig.17 The Tafel data comparison of porous titanium carbide loaded with molybdenum disulfide and unloaded porous titanium carbide for electrocatalytic hydrogen evolution is shown in the figure. The Tafel slope of the original ceramic membrane is 294mV / dec. After loading the catalyst, the spin coating method is 145mV / dec, the electrodeposition method is 151mV / dec, and the hydrothermal method is 141mV / dec. The performance of hydrogen evolution from water has been greatly improved.
[0076] Example 3
[0077] This embodiment provides a preparation method of porous titanium carbide ceramic loaded with molybdenum disulfide and a hydrogen production test, which are as follows:
[0078] 55.8 g of titanium carbide powder with an average particle size of 8 μm, 1.2 g of silicon carbide powder and 3 g of yttrium oxide powder, 7.5 g of polyethersulfone as a polymer binder, 2.4 g of O-(2-aminopropyl)-O'-(2-methoxyethyl)polypropylene glycol as a dispersant, and 30.1 g of N-methylpyrrolidone as a solvent were selected, and a slurry with a solid content of 60% was poured into a ball mill, and alumina ball mill beads were added. The ball mill speed was set to 200 r / min and run for 36 hours; the ball-milled slurry was placed on a tape-casting equipment designed and assembled in the laboratory for tape-casting, the scraper height was adjusted to 0.8 mm, and then placed in water for curing for 4 hours. After solidification, several circular bodies with a radius of 1 cm were cut from the green body and placed in an oven at 80°C for 4 hours. The dried bodies were placed in a vacuum carbon tube furnace, and heated to 1650°C at a rate of 14°C / min in a nitrogen atmosphere, and kept warm for 4 hours. After cooling to room temperature, a sintered circular porous titanium carbide ceramic membrane was obtained.
[0079] Weigh 0.86g of thiourea and 0.5g of ammonium molybdenum sulfate, add 40ml of deionized water, adjust pH≈3 with 0.1mol / L hydrochloric acid, stir for 30min, pour into a polytetrafluoroethylene stainless steel autoclave, put in the sintered circular porous titanium carbide ceramic membrane, put in an oven, the reaction temperature is 200℃, the reaction time is 12h. After the reaction, take out, wash with alcohol and water three times each, and obtain a porous titanium carbide ceramic loaded with molybdenum disulfide prepared by a hydrothermal method.
[0080] Weigh 1.928g (NH4)6Mo7O 24 ·4g H2O and 1.76g K2S, add hydrochloric acid to pH≈8, add a certain amount of deionized water to prepare an electrolyte, use a saturated calomel electrode as a reference electrode, a graphite rod as a counter electrode, and a sintered circular porous titanium carbide ceramic membrane as a working electrode. Put it into the electrolyte, set the chronopotentiometry electrodeposition for 600s, and obtain the porous titanium carbide ceramic loaded with molybdenum disulfide prepared by electrochemical deposition.
[0081] Weigh 0.2g of ammonium tetrathiomolybdate and 9.8g of ethylene glycol to prepare an ethylene glycol solution containing 2% ammonium tetrathiomolybdate by mass concentration, take the sintered circular porous titanium carbide ceramic membrane, set the rotation speed to 1500rpm, spin coat it on the surface of the ceramic sheet, bake in an oven at 100°C for 100min, and reduce it in a nitrogen and hydrogen (5% H2+95% N2) atmosphere at 450°C for 2h to obtain a porous titanium carbide ceramic loaded with molybdenum disulfide prepared by spin coating.
[0082] Example 4
[0083] This embodiment provides a preparation method of a porous titanium nitride ceramic loaded with molybdenum disulfide and a hydrogen production test, which are as follows:
[0084] Titanium nitride powder with an average particle size of 5 μm, yttrium oxide powder and titanium dioxide powder accounting for 7% of the mass of the titanium nitride powder (molar ratio of 1:1), polyvinyl pyrrolidone accounting for 4% of the mass of the titanium nitride powder as a dispersant, polyether sulfone accounting for 16% of the mass of the titanium nitride powder as a binder, and N-methylpyrrolidone accounting for 65% of the mass of the titanium nitride powder as a solvent are selected and poured into a ball mill for ball milling. The ball mill speed is 200 r / min and the operation time is 36 hours. The ball-milled slurry is placed on a tape-casting equipment designed and assembled in the laboratory for tape-casting, the scraper height is adjusted to 1.2 mm, and then placed in water for curing for 10 hours. The cured green body is placed at room temperature for drying for 48 hours. The dried green body is heated to 1600°C at a heating rate of 12°C / min in a nitrogen furnace and kept warm for 4 hours to obtain a porous titanium nitride ceramic. Weigh ammonium molybdate tetrahydrate and thiourea (mass ratio of 1:0.86), add deionized water, add hydrochloric acid to adjust the pH to 3, put them into a polytetrafluoroethylene stainless steel autoclave together with the porous titanium nitride ceramic, and then put them into an oven, the reaction temperature is 180°C, and the reaction time is 20h. The porous titanium nitride ceramic loaded with molybdenum disulfide is obtained, washed with deionized water, and dried at 80°C.
[0085] The double-layer capacitance of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide in this embodiment is 115.8 mF cm -2, indicating that the electrode prepared in this embodiment provides a larger reaction area in the electrochemical process and accelerates the reaction rate; the transfer resistance of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide prepared in this embodiment is 9Ω; at 0.5 mol L - 1 The electrocatalytic hydrogen evolution test in H2SO4 solution found that the current density was 10mAcm -2 The hydrogen evolution overpotential of the electrode prepared by the present invention is 217 mV (vs RHE).
[0086] Example 5
[0087] This embodiment provides a preparation method of a porous titanium nitride ceramic loaded with molybdenum disulfide and a hydrogen production test, which are as follows:
[0088] Titanium nitride powder with an average particle size of 10 μm, alumina powder and titanium dioxide powder accounting for 10% of the mass of the titanium nitride powder (molar ratio of 1:1), polyvinyl pyrrolidone accounting for 5% of the mass of the titanium nitride powder as a dispersant, polyether sulfone accounting for 18% of the mass of the titanium nitride powder as a binder, and N-methylpyrrolidone accounting for 68% of the mass of the titanium nitride powder as a solvent are selected and poured into a ball mill for ball milling. The ball mill speed is 180 r / min and the operation is carried out for 30 hours; the ball-milled slurry is placed on a tape-casting molding equipment designed and assembled in the laboratory for tape-casting, the scraper height is adjusted to 2 mm, and then placed in water for curing for 10 hours. The cured green body is placed at room temperature for drying for 48 hours; the dried green body is heated to 1700°C at a heating rate of 15°C / min in a nitrogen furnace and kept warm for 5 hours to obtain a porous titanium nitride ceramic. Weigh ammonium molybdate tetrahydrate and thiourea (mass ratio of 1:2), add deionized water, add hydrochloric acid to adjust the pH to 2, put them into a polytetrafluoroethylene stainless steel autoclave together with the porous titanium nitride ceramic, and then put them into an oven, the reaction temperature is 160°C, and the reaction time is 15h. The porous titanium nitride ceramic loaded with molybdenum disulfide is obtained, washed with deionized water, and dried at 80°C.
[0089] The double layer capacitance of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide in this embodiment is 104.2 mF cm -2 , indicating that the electrode prepared in this embodiment provides a larger reaction area in the electrochemical process and accelerates the reaction rate; the transfer resistance of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide prepared in this embodiment is 16Ω; at 0.5 mol L - 1 The electrocatalytic hydrogen evolution test in H2SO4 solution found that the current density was 10mAcm -2 The hydrogen evolution overpotential of the electrode prepared by the present invention is 208 mV (vs RHE).
[0090] Example 6
[0091] The following examples are all carried out on the basis of the porous titanium nitride ceramic membrane obtained in Example 1.
[0092] Prepare a solution of 0.01mL H2O and 100mL C2H5OH, stir at high speed for 10 minutes, and stir thoroughly. Then, add a mixed solution of n-butyl titanate (TBOT) and tetraethyl orthosilicate (TEOS) dropwise into a mixed solution of ethanol and water. Continue stirring for one hour to obtain a sol of titanic acid / silicic acid. Add a porous titanium nitride ceramic membrane, and then transfer the mixed solution into a stainless steel hydrothermal autoclave lined with polytetrafluoroethylene for hydrothermal treatment. Set the hydrothermal temperature to 180°C and keep warm for 6 hours to obtain a porous titanium nitride ceramic membrane modified with TiO2.
[0093] The porous titanium nitride ceramic membrane with a TiO2 mass fraction of 1.2% was photocatalytically reacted with a 15% methanol solution under the irradiation of a 300W xenon lamp, and the hydrogen production rate was 92mmol·h -1 ·m -2 .
[0094] Example 7
[0095] The following examples are all carried out on the basis of the porous titanium nitride ceramic membrane obtained in Example 1.
[0096] Weigh 125 mg of ammonium tetrathiomolybdate and 9.725 g of sodium chloride, add a certain amount of deionized water, prepare an electrolyte with an ammonium tetrathiomolybdate concentration of 5%, use a saturated calomel electrode as a reference electrode, a graphite rod as a counter electrode, and a titanium nitride porous ceramic as a working electrode, insert them into the electrolyte, set the chronopotentiometry potential to -0.3 V, and the time to 1000 s. The product is repeatedly washed three times with deionized water and ethanol, respectively, and dried at 60°C to obtain a porous titanium nitride ceramic loaded with molybdenum disulfide.
[0097] The double-layer capacitance of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum sulfide in this embodiment is 84.5 mF cm -2 , indicating that the electrode prepared in this embodiment provides a larger reaction area in the electrochemical process and accelerates the reaction rate; the transfer resistance of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide prepared in this embodiment is 34Ω; at 0.5 mol L -1 The electrocatalytic hydrogen evolution test in H2SO4 solution found that the current density was 10mAcm -2 The hydrogen evolution overpotential of the electrode prepared by the present invention is 224 mV (vsRHE).
[0098] Example 8
[0099] The following examples are all carried out on the basis of the porous titanium nitride ceramic membrane obtained in Example 1.
[0100] Weigh 185 mg of ammonium tetrathiomolybdate and 5.24 g of ethylene glycol to prepare an ethylene glycol solution containing 10 wt% ammonium tetrathiomolybdate, set the rotation speed to 1500 rpm, spin coat on the surface of the porous titanium nitride ceramic, bake in an oven at 80°C for 50 min, place in a tubular furnace and reduce for 3 h in a nitrogen and hydrogen (5% H2+95% N2) atmosphere at 450°C, and cool to room temperature to obtain a porous titanium nitride ceramic loaded with molybdenum disulfide.
[0101] The double layer capacitance of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum sulfide in this embodiment is 117.4 mF cm -2 , indicating that the electrode prepared in this embodiment provides a larger reaction area in the electrochemical process and accelerates the reaction rate; the transfer resistance of the porous titanium nitride electrocatalytic hydrogen evolution electrode supported by molybdenum disulfide prepared in this embodiment is 28Ω; at 0.5 mol L -1 The electrocatalytic hydrogen evolution test in H2SO4 solution found that the current density was 10mAcm -2 The hydrogen evolution overpotential of the electrode prepared by the present invention is 213 mV (vs RHE).
Claims
1. A method for preparing a porous conductive ceramic membrane loaded with a photoelectric catalyst, characterized in that: The preparation method comprises the following steps: (1) ball-milling and mixing a conductive ceramic powder, a sintering aid, a dispersant, a binder, and a solvent to obtain a ceramic slurry; wherein the conductive ceramic powder is selected from one or two of titanium nitride and titanium carbide; and the sintering aid is one or more of yttrium oxide, titanium dioxide, silicon carbide, and aluminum oxide; (2) The ceramic slurry is subjected to tape casting, curing and drying to obtain a ceramic membrane blank; (3) sintering the ceramic membrane green body to prepare a porous conductive ceramic membrane; wherein the sintering is performed in a carbon tube furnace filled with nitrogen and the sintering temperature is 1500-1700° C.; (4) A photoelectrocatalyst is loaded on the porous conductive ceramic membrane to obtain a porous conductive ceramic membrane loaded with a photoelectrocatalyst; the method for loading the photoelectrocatalyst is selected from a hydrothermal method, an electrochemical deposition method, and a spin coating method, and the loaded photoelectrocatalyst includes molybdenum disulfide.
2. The method for preparing a porous conductive ceramic membrane loaded with a photoelectrocatalyst according to claim 1, characterized in that: The porosity of the porous conductive ceramic membrane is 60-70%.
3. The method for preparing a porous conductive ceramic membrane loaded with a photoelectrocatalyst according to claim 1 or 2, characterized in that: In step (1), the particle size of the conductive ceramic powder is 2-10 μm.
4. The method for preparing a porous conductive ceramic membrane loaded with a photoelectrocatalyst according to claim 1, characterized in that: In step (1), the dispersant is selected from one or more of polyvinyl pyrrolidone, KD-1 dispersant and O-(2-aminopropyl)-O`-(2-methoxyethyl) polyethylene glycol.
5. The method for preparing a porous conductive ceramic membrane loaded with a photoelectrocatalyst according to claim 1, characterized in that: In step (1), the binder is selected from one or more of polyethersulfone, polyvinyl butyral and polyvinyl alcohol.
6. The method for preparing a porous conductive ceramic membrane loaded with a photoelectrocatalyst according to claim 1, characterized in that: In step (1), the solvent includes N-methylpyrrolidone.
7. The method for preparing a porous conductive ceramic membrane loaded with a photoelectrocatalyst according to claim 1, characterized in that: In step (1), the ball milling speed is 100-300 r / min, and the ball milling time is 10-48 h.
8. The method for preparing a porous conductive ceramic membrane loaded with a photoelectrocatalyst according to claim 1, characterized in that: The casting operation in step (2) comprises the following steps: The ceramic slurry is subjected to vacuum degassing treatment, and then transferred to a casting mold, the scraper height is adjusted, and after casting, it is placed in water, completely solidified, and dried to form a ceramic membrane blank.
9. The method for preparing a porous conductive ceramic membrane loaded with a photoelectric catalyst according to claim 8, characterized in that: The scraper height is adjusted to 0.1-10 mm.
10. The method for preparing a porous conductive ceramic membrane loaded with a photoelectrocatalyst according to claim 1, characterized in that: The heating rate of the carbon tube furnace is 10-15°C / min, and the holding time after heating to the sintering temperature is 4-10h.
11. The method for preparing a porous conductive ceramic membrane loaded with a photoelectrocatalyst according to claim 1, characterized in that: The hydrothermal method comprises the following steps: Add ammonium molybdate tetrahydrate, thiourea and deionized water to mix with the porous conductive ceramic membrane, adjust the pH, transfer to a reactor for hydrothermal reaction, wash the product with deionized water and ethanol and dry it to obtain a porous conductive ceramic membrane loaded with molybdenum disulfide.
12. The method for preparing a porous conductive ceramic membrane loaded with a photoelectrocatalyst according to claim 11, characterized in that: The mass ratio of the ammonium molybdate tetrahydrate to thiourea is 1:(0.8-2.6).
13. The method for preparing a porous conductive ceramic membrane loaded with a photoelectrocatalyst according to claim 11, characterized in that: The pH value is 1-5.
14. The method for preparing a porous conductive ceramic membrane loaded with a photoelectrocatalyst according to claim 11, characterized in that: The hydrothermal reaction temperature is 140-200° C., and the hydrothermal reaction time is 12-24 hours.
15. The method for preparing a porous conductive ceramic membrane loaded with a photoelectrocatalyst according to claim 1, characterized in that: The electrochemical deposition method comprises the following steps: Ammonium tetrathiomolybdate, sodium chloride and deionized water are added to prepare an electrolyte, and a three-electrode system is adopted to perform electrodeposition with a porous conductive ceramic membrane as a working electrode. The product is washed and dried with deionized water and ethanol to obtain a porous conductive ceramic membrane loaded with molybdenum disulfide.
16. The method for preparing a porous conductive ceramic membrane loaded with a photoelectrocatalyst according to claim 15, characterized in that: The mass concentration of ammonium tetrathiomolybdate prepared by the electrochemical deposition method is 1%-10%, and the three-electrode system includes a working electrode, a reference electrode and a counter electrode, wherein the reference electrode includes a saturated calomel electrode, the counter electrode includes a graphite rod, the electrodeposition mode is a chronopotentiometry, and the electrodeposition time is 500-2400s.
17. The method for preparing a porous conductive ceramic membrane loaded with a photoelectric catalyst according to claim 1, characterized in that: The spin coating method comprises the following steps: Ammonium tetrathiomolybdate and ethylene glycol were added to form a uniform solution, and a specific spin coater speed was set to spin coat the porous conductive ceramic membrane. After drying, the solution was placed in a tubular furnace under a nitrogen and hydrogen atmosphere for reduction to obtain a porous conductive ceramic membrane loaded with molybdenum disulfide.
18. The method for preparing a porous conductive ceramic membrane loaded with a photoelectrocatalyst according to claim 17, characterized in that: The mass concentration of the ammonium tetrathiomolybdate is 1%-20%, the spin coater speed is set to 1000-3000r / min, the drying temperature is 60-100°C, the drying time is 30min-200min, the atmosphere in the tubular furnace includes 5% hydrogen and 95% nitrogen by volume percentage, the reduction temperature is 300-500°C, and the reduction time is 1-5h.
19. A porous conductive ceramic membrane loaded with photoelectrocatalyst prepared by the method for preparing a porous conductive ceramic membrane loaded with photoelectrocatalyst according to any one of claims 1 to 18.
20. Use of the porous conductive ceramic membrane loaded with photoelectrocatalyst according to claim 19 in hydrogen production by hydrolysis.
Citation Information
Patent Citations
Method for preparing ceramic membrane supported TiO2 material
CN105964234A
Method for preparing hydrophobic porous cordierite ceramic membrane for desalination by using high-silicon solid waste as raw material through tape casting
CN110893324A